Structural analyses and photovoltaic device simulations in two and three dimensions applied to Ag-alloyed Cu(In,Ga)Se2 solar cells - Chang-Yun Song; Zelong Wang; Matthias Maiberg; Heiko Kempa; Julia Horstmann; Wolfram Witte; Rico Gutzler; Dimitrios Hariskos; Daniel Abou-Ras; Sinju Thomas; Roland Scheer; Ali Gholinia (JPhys Energy)
The present study reports on the structural changes and related photovoltaic properties resulting from the addition of Ag in Cu(In,Ga)Se _2 (CIGS)-based thin-film solar cells analysed using two-dimensional (2D) and three-dimensional (3D) analytical and modelling techniques. The microstructures of CIGS and Ag-containing CIGS (ACIGS) layers were characterized by means of 2D and 3D electron backscatter diffraction (EBSD). Ag addition significantly increased grain sizes, which is differently observed in the 2D and 3D EBSD analyses due to the different methodology. Moreover, opto-electronic 3D device simulations, which incorporate real 3D structural data obtained from 3D EBSD, confirmed that 2D models tend to underestimate the impact of grain boundaries on the device performance. Device simulations showed that the increased grain size and thus, the decreased grain-boundary density, resulting from Ag addition had a positive effect on the open-circuit voltage ( V _OC ) of the solar cell. The V _OC improvement was more pronounced in ACIGS layers of high minority-carrier lifetimes. These findings highlight the necessity of combining 3D EBSD analysis with 3D device simulations to optimize the relationship between microstructural characteristics and photovoltaic performance in solar cells to understand opto-electronic properties more quantitatively.